Vivência em um curso de extensão de Espanhol-LE interpretada pelo viés da complexidade: reflexões, descobertas e complexificação de uma pesquisadora - Coelho, Priscila Penna Ferreira (2019)
The aim of this research is to describe and interpret the phenomenon experience in an extension course that emerged from the literary work Cien años de soledad, by Garcia Marquez, that explores the association between linguistic and literary-cultural issues, as well as an emphasis on teacher education. The course, that approached on-site and distance learning activities was offered to undergraduates of the Languages Course, major in Spanish, in a Municipal College in the interior of São Paulo State. The research is based on the complexity epistemology, (MORIN, 2011, 2015a, 2015b, 2015c), on transdisciplinarity and on teacher education (MORAES, 2008), on the concepts of complex-based design (BEHRENS, 2005, 2006; FREIRE 2013), and in the literature in view of complexity (MORIN, 2005; CÂNDIDO, 1999, 2002; COSSON, 2014). Concerning the methodological view it was based on the Complex Hermeneutic-Phenomenological Approach (FREIRE 2010, 2012, 2017a), in order to answer the following research question: What is the nature of the undergraduates of the Languages Course, major in Spanish in an extension course based on the literary work Cien años de soledad, which explores linguistic and literary-cultural issues, as well as emphasizes the teacher education? The course designed based on the perception of the complexity present in the chosen literary work, was divided into five modules and a final reflexive recursive meeting. The deep immersion (FREIRE, 2012) carried out during the studied phenomenon description and interpretation allowed the development of a reflexive process that concluded that the course taught was not totally based on the complexity theory and the interpretative process does not exactly follow the proposed approach adopted. The whole process was redone to meet the theoretical assumptions intended for a research. The findings show that this study not only presents the description and interpretation of a phenomenon of human experience, highlighting the essence of the experience in an extension course that sought to explore the association between linguistic and literary-cultural issues, as well as the awareness of teacher education, but simultaneously represents a meta-research, unveiling the complexification process experienced by the researcher